Implementation of Design Thinking in Media Development “Kaca” (Kartu Baca) - Sari, Intan Permata; Azizah, Amelinda Myrna Nur (Universitas Pendidikan Indonesia (UPI), 2024)
One of the skills that must be achieved in low-grade elementary school students is reading. In reality, in learning there are still many low-grade students who are not able to read well. Low-grade elementary school students still need guidance from teachers in learning reading skills. Beginning reading skills are not just seeing a bunch of letters arranged into words, groups of words, sentences, paragraphs and discourse alone, but reading skills are activities to understand and interpret symbols, symbols, signs, writing that has meaning so that readers can understand the message conveyed. The purpose of this research is to design Reading Cards as a game-based learning media by applying the concept of Boardgames. In the process of developing learning media, the author uses the design thinking innovation method. Game-based learning media can utilize technology as an interactive and interesting learning media. The design of learning media KACA (Kartu Baca) is considered appropriate to improve the reading ability of students as users.